2019
DOI: 10.3390/ijerph16152650
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Alcohol and Knowledge of Cardiovascular Diseases among Ellisras Rural Children Aged 14–22 Years: Ellisras Longitudinal Study

Abstract: The harm alcohol abuse does to physical and mental health is well established. The perception of cardiovascular disease risk factors and alcohol use requires attention. This study aims to investigate the association between alcohol usage and knowledge of cardiovascular diseases (CVDs) risk factors among Ellisras rural adolescents and young adults aged 14–22 years. In this cross-sectional study a total of 1409 subjects (736 boys and 673 girls), aged 14–22 years, from the Ellisras Longitudinal Study, South Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…It is, therefore, in this context that the present study aimed to determine, in black South African children aged 8 to 17 years in the Ellisras Longitudinal Study, whether indices of central (waist circumference), general (body mass index), or subcutaneous (skin-fold thickness) adiposity independently predicted BP at multiple points. This is particularly pertinent, given that Ellisras is reported to be dominated by cardiovascular risk factors, including among others, overweight or obesity and hypertension [7,8]. Researching this issue is of major interest to public health and has important policy implications in ensuring the health of young people today and adults of tomorrow.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, in this context that the present study aimed to determine, in black South African children aged 8 to 17 years in the Ellisras Longitudinal Study, whether indices of central (waist circumference), general (body mass index), or subcutaneous (skin-fold thickness) adiposity independently predicted BP at multiple points. This is particularly pertinent, given that Ellisras is reported to be dominated by cardiovascular risk factors, including among others, overweight or obesity and hypertension [7,8]. Researching this issue is of major interest to public health and has important policy implications in ensuring the health of young people today and adults of tomorrow.…”
Section: Introductionmentioning
confidence: 99%
“…The National Institute on Alcohol Abuse and Alcoholism defined binge drinking as drinking >4 drinks per day for females and >5 drinks per day for males [ 24 ]. In the current Ellisras cohort, communal drinkers were more prevalent during weekends, for example, Fridays (4.9% for males and 7.3% for females) and Saturdays (6.1% for males and 7.7% for females), with females significantly higher on Fridays ( p < 0.049) compared to males [ 10 ]. In the literature, it was found that men were more likely to consume alcohol consistently, since they presumably experienced more social problems.…”
Section: Discussionmentioning
confidence: 99%
“…The Ellisras Longitudinal Study (ELS) design and sampling methodology has been reported elsewhere [ 10 , 12 ]. A quantitative study applying a cross-sectional design was conducted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Physical Activity and Health Longitudinal (PAHL) study from A Monyeki et al [22], the Ellisras Longitudinal Study (ELS) from K Monyeki et al [23], and the Analysis of Behaviours of Children During Growth (ABCD-Growth study) [24] from Fernandes are three examples of recent longitudinal studies set up in other countries with new and modern techniques. They show that pediatric exercise science will bloom in the near future.…”
Section: Other Recent Longitudinal Studiesmentioning
confidence: 99%